1998
DOI: 10.1016/s0014-5793(98)00902-8
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Ca2+ influx reveal the duality of events underlying the activation by vanadate and fluoride of the Gárdos effect in human red blood cells

Abstract: . Substitution of Na + by K + inhibited the RS Ca 2+ influx induced by NaVO Q but stimulated that by NaF. The NaVO Qinduced Ca 2+ influx was sensitive to nifedipine (IC SH = 50 mol/l), Cu 2+ (IC SH = 9 mol/l), DTNB (5,5P-dithiobis-(dinitrobenzoic acid)) (IC SH = 12 mol/l) (maximal inhibition 16%, 18%, and 28%, respectively, if NaF was used as inducer). On the other hand, tetrodotoxin (TTX) and cyclosporin A inhibited only the NaF-induced RS Ca 2+ influx (IC SH = 21 mol/l and 28 mol/l, respectively). Pig RBC, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The time course of the increase in Na ϩ permeability that occurs with exposure of human red blood cells to Ca 2ϩ plus CCh correlates with the time course (initial increase) of changes in Ca 2ϩ and cGMP content (41). Whether the pattern of these changes applies to the Ca 2ϩ plus F Ϫ case is not known although the transient increase in a TTX-sensitive Ca 2ϩ uptake has been correlated with the Na ϩ permeability changes (17). The implication here is that activation of muscarinic receptors by means of G proteins such as G i , G s , and G q , which are known to be present in human red blood cell membranes (8 -14), uses the same Na ϩ channels as does the activation by the combination Ca 2ϩ plus F Ϫ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time course of the increase in Na ϩ permeability that occurs with exposure of human red blood cells to Ca 2ϩ plus CCh correlates with the time course (initial increase) of changes in Ca 2ϩ and cGMP content (41). Whether the pattern of these changes applies to the Ca 2ϩ plus F Ϫ case is not known although the transient increase in a TTX-sensitive Ca 2ϩ uptake has been correlated with the Na ϩ permeability changes (17). The implication here is that activation of muscarinic receptors by means of G proteins such as G i , G s , and G q , which are known to be present in human red blood cell membranes (8 -14), uses the same Na ϩ channels as does the activation by the combination Ca 2ϩ plus F Ϫ .…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that heterotrimeric G proteins of several types (e.g., G i , G o , G q ) are present in human red blood cells (8)(9)(10)(11)(12)(13)(14); in addition, these cells are also known to contain Ϸ2.7 M Al 3ϩ ͞l.rbc (15), which may be necessary for adenylyl cyclase activation (16). It was further shown that, under conditions where the Na ϩ flux was increased in the presence of added F Ϫ and Ca 2ϩ , Ca 2ϩ uptake (measured with 45 Ca 2ϩ ) was also increased and could be inhibited with TTX (17). A similar TTX-sensitive Ca 2ϩ influx has been characterized in cardiac myocytes (18).…”
mentioning
confidence: 99%